2020
DOI: 10.1002/slct.201904931
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Based Copper‐Nickel Bimetal Nanocomposite: Magnetically Separable Catalyst for Reducing Hexavalent Chromium

Abstract: Graphene based copper‐nickel bimetal nanocomposite (Cu3Ni2‐rGO) was prepared via a one‐step solvothermal procedure, in which Ni(OH)2 and Cu(OH)2 were used as precursors. Structural characterization confirms that the as‐prepared Cu3Ni2‐rGO nanocomposite is composed of Cu3Ni2 nanoparticles in the size range of 20–100 nm and the reduced graphene oxide (rGO) sheets. Benefiting from the combination of Cu3Ni2 and rGO, the Cu3Ni2‐rGO nanocomposite exhibits excellent catalytic performance on reducing highly toxic Cr(V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Similarly Li et al (2016c) studied catalytic Cr(VI) reduction by oxalic acid at different pH values ranging from 2 to 7 under similar reaction conditions and reported pH = 2 as optimum pH for rapid conversion of Cr(VI) to Cr(III). Yao et al (2020) have recently reported effect of pH of the medium on catalytic Cr(VI) reduction to Cr(III) with formic acid using RGO supported Cu-Ni bimetallic nanoparticles as catalyst and have found exactly same trend of pH dependence of reduction of Cr(VI). They also reduced Cr(VI) with different reducing agents including methanol (neutral), citric acid (pH = 1.0) and sodium borohydride (pH = 8) but formic acid (pH = 2) was found to be the best one because of its dual role in reduction process.…”
Section: Factors Affecting the Apparent Rate Constant (K Apmentioning
confidence: 65%
See 3 more Smart Citations
“…Similarly Li et al (2016c) studied catalytic Cr(VI) reduction by oxalic acid at different pH values ranging from 2 to 7 under similar reaction conditions and reported pH = 2 as optimum pH for rapid conversion of Cr(VI) to Cr(III). Yao et al (2020) have recently reported effect of pH of the medium on catalytic Cr(VI) reduction to Cr(III) with formic acid using RGO supported Cu-Ni bimetallic nanoparticles as catalyst and have found exactly same trend of pH dependence of reduction of Cr(VI). They also reduced Cr(VI) with different reducing agents including methanol (neutral), citric acid (pH = 1.0) and sodium borohydride (pH = 8) but formic acid (pH = 2) was found to be the best one because of its dual role in reduction process.…”
Section: Factors Affecting the Apparent Rate Constant (K Apmentioning
confidence: 65%
“…Some other factors like nature of reducing agent, nature of supports used for stabilization of nano-catalysts, weight ratio of metal nanoparticles to supports, content of Cr(VI) and reducing agents may also affect the rate of reduction of Cr(VI) ( Yao et al, 2020 ) but data reported on such kind of factors is limited and has not been discussed in this report. Role of such kind of factors is not much clear and needs further studies for optimization of process parameters to carry out reduction of Cr(VI) at large scale.…”
Section: Factors Affecting the Apparent Rate Constant (K Apmentioning
confidence: 97%
See 2 more Smart Citations
“…[6] Nowadays, to promote the application of nanoparticles, the preparation of copper and their oxides has been investigated extensively. [7] Furthermore, copper-containing compounds with the spinel-type structure and also magnetic nanoparticles have a potential catalytic application. [8,9] Developing a simple method to assemble nanoparticles with well dispersion and stability, and their immobilization on active support is desirable methodology from the viewpoint of green synthesis and manufacturing cost.…”
Section: Introductionmentioning
confidence: 99%